Quantification and scales in change - Gergel, Remus; Watkins, Jonathan (Language Science Press, 2020)
This volume contains thematic papers on semantic change which emerged from the second edition of Formal Diachronic Semantics held at Saarland University. Its authorship ranges from established scholars in the field of language change to advanced PhD students whose contributions have equally qualified and have been selected after a two-step peer-review process. The key foci are variablity and diachronic trajectories in scale structures and quantification, but readers will also find a variety of further (and clearly non-disjoint) issues covered including reference, modality, givenness, presuppositions, alternatives in language change, temporality, epistemic indefiniteness, as well as - in more general terms - the interfaces of semantics with syntax, pragmatics and morphology. Given the nature of the field, the contributions are primarily based on original corpus studies (in one case also on synchronic experimental data) and present a series of new findings and theoretical analyses of several languages, first and foremost from the Germanic and Romance subbranches of Indo-European (English, French, German, Italian, Spanish) and from Semitic (with an analysis of universal quantification in Biblical Hebrew).